A critical analysis of the purported role of hypoxaemia in the comorbidity of obstructive sleep apnoea and epilepsy. (10th November 2020) - Mishra, Priyadarshini; Jaseja, Harinder; Goyal, Manish
Abstract: Obstructive sleep apnoea (OSA) is a globally prevalent sleep disorder of significant health concern and confounded with several comorbidities resulting in adverse effect(s) on quality of life in patients afflicted with it. Of particular interest is the enigmatic high comorbidity of OSA with epilepsy, the exact underlying pathophysiology of which remains elusive despite a multitude of research performed in the last four decades. Hypoxaemia, which is an important characteristic feature found in OSA during apnoeic spells, has been implicated in the high comorbidity of OSA with epilepsy, the basis of which rests upon hypoxaemia‐mediated brain damage, subcortical release phenomenon, oxidative stress and neuroinflammatory reactions. However, several studies present contradictory evidences that potentially refute the hypoxaemia‐based mechanism. Additionally, the role of hypercapnia thatgenerally accompanies hypoxaemia during apnoeic spells, cannot be overlooked and is known to be potentially protective against neuronal hyperexcitability. Thus, hypoxaemia theory implicated in the high comorbidity of OSA and epilepsy appears weak and refutable. This brief paper studies and critically analyses the role of hypoxaemia in conjunction with hypercapnia in the underlying pathophysiology of the comorbidity.